New Insight into Cerebrovascular Diseases An Updated Comprehensive Review - Bozzetto Ambrosi, Patricia; Ahmad, Rufai; Abdullahi, Auwal; Agrawal, Amit (IntechOpen, 2020)
"Brain circulation is a true road map that consists of large extended navigation territories and a number of unimagined and undiscovered routes." Dr. Patricia Bozzetto Ambrosi This book combines an update on the review of cerebrovascular diseases in the form of textbook chapters, which has been carefully reviewed by Dr. Patricia Bozzetto Ambrosi, Drs. Rufai Ahmad and Auwal Abdullahi and Dr. Amit Agrawal, high-performance academic editors with extensive experience in neurodisciplines, including neurology, neurosurgery, neuroscience, and neuroradiology, covering the best standards of neurological practice involving basic and clinical aspects of cerebrovascular diseases. Each topic was carefully revised and prepared using smooth, structured vocabulary, plus superb graphics and scientific illustrations. In emphasizing the most common aspects of cerebrovascular diseases: stroke burden, pathophysiology, hemodynamics, diagnosis, management, repair, and healing, the book is comprehensive but concise and should become the standard reference guide for this neurological approach.